Freehold : defiance - Williamson, Michael Z.; Williamson, Michael Z.; Ibson, Jamie; Green, Jonathon; Anderson, Kevin J., 1962-; Ikenberry, Kevin; Schlenker, Jessica; DiNote, Jaime; McCaskey, William; Watson, Justin; Holmes, J.F; Cordova, Jason, 1978-; et al. (Williamson, Michael Z. Freehold, 2022)
"War for a planet--and a way of life. The UN has invaded the Freehold of Grainne, a bastion of libertarian government in a galaxy of authoritarianism. Grainne must form an organized force from the shattered remnants of their military and from grimly determined, but underequipped and outnumbered, insurgents. Their war is for their very way of life. They'll do everything and anything to stop this invasion, using whatever means are available. They mean to make the enemy suffer. Quod vulnera curare potes. Physical wounds heal. But defiance? Defiance is to the death--or victory!"--